STUDENTS’ PERCEPTION OF ENGLISH DAY AND SPEAKING SKILL AT ASH-SHIDDIIQI ISLAMIC BOARDING SCHOOL - Nurul Izzatil Ulya (JR-ELT (Journal of Research in English Language Teaching), 2023)
The research aimed to investigate the impact of English Day on students' speaking skills in Islamic schools, using questionnaires to gather data on students' perceptions of English Day. The results showed that English Day positively affects speaking skills, with students strongly agreeing and agreeing that it is effective in familiarizing them with speaking English, providing wider opportunities to explore their language skills, and building their conceptual knowledge in English. The majority of students also agreed that learning activities in English Day are more effective in improving their English skills, and they can learn more optimally in the English Day program. The learning conditions on English Day were found to be more interesting compared to regular English classes, and students agreed that English learning on English Day is more contextualized through activities related to daily activities. The concept of reward and punishment in English Day was perceived as providing more motivation for students to improve their English skills. Based on the questionnaire results, the researcher concluded that 100 students contributed to English Day, and they gave a positive response or agreed that English clubs can support their speaking skills. The findings align with the benefits of joining extracurricular English clubs, as identified in previous research.